Use of Photobioreactors in Regenerative Life Support Systems for Human Space Exploration - Fahrion, Jana; Mastroleo, Felice; Dussap, Claude-Gilles; Leys, Natalie (Frontiers in Microbiology, 2021)
There are still many challenges to overcome for human space exploration beyond low Earth orbit (LEO) (e.g. to the Moon) and for long-term missions (e.g. to Mars). One of the biggest problems is the reliable air, water and food supply for the crew. Bioregenerative life support systems (BLSS) aim to overcome these challenges using bioreactors for waste treatment, air and water revitalization as well as food production. In this review we focus on the microbial photosynthetic bioprocess and photobioreactors in space, which allow removal of toxic carbon dioxide (CO2) and production of oxygen (O2) and edible biomass. This paper gives an overview of the conducted space experiments in LEO with photobioreactors and the precursor work (on ground and in space) for BLSS projects over the last 30 years. We discuss the different hardware approaches as well as the organisms tested for these bioreactors. Even though a lot of experiments showed successful biological air revitalization on ground, the transfer to the space environment is far from trivial. For example, gas-liquid transfer phenomena are different under microgravity conditions which inevitably can affect the cultivation process and the oxygen production. In this review, we also highlight the missing expertise in this research field to pave the way for future space photobioreactor development and we point to future experiments needed to master the challenge of a fully functional BLSS.